Diaconal Services for Congregants in Need of Emotional and Spiritual Support at GPEI Bitung - Aitkobo, Dhion Deversen; Sonata, Beta Ria (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2025)
This study explores the role of diaconia in providing emotional an spiritual support to the congregation at GPEI Bitung. By implementing community services such as home visits, prayer gatherings, and Bible study groups, the congregation has strengthened emotional bonds between the pastor and the congregation, particularly those facing challenges like health or financial issues. The results show significant improvements in emotional and spiritual growth, engagement in church activities, and stronger interpersonal relationships within the community. Diaconia effectively nurtures solidarity, builds a caring environment, and enhances spiritual maturity within the congregation. The challenges faced include limited human resources and operational funding. This study emphasizes the importance of holistic ministry and recommends the replication of the program with contextual adaptations. Penelitian ini mengkaji peran diakonia dalam memberikan dukungan emosional dan spiritual kepada jemaat di GPEI Bitung. Melalui pelaksanaan pelayanan masyarakat seperti kunjungan rumah, pertemuan doa, dan kelompok belajar Alkitab, jemaat telah memperkuat ikatan emosional antara pendeta dan jemaat, khususnya mereka yang menghadapi tantangan seperti masalah kesehatan atau keuangan. Hasilnya menunjukkan peningkatan yang signifikan dalam pertumbuhan emosional dan spiritual, keterlibatan dalam kegiatan gereja, dan hubungan interpersonal yang lebih kuat dalam komunitas. Diakonia secara efektif memelihara solidaritas, membangun lingkungan yang peduli, dan meningkatkan kedewasaan spiritual dalam jemaat. Tantangan yang dihadapi meliputi keterbatasan sumber daya manusia dan dana operasional. Penelitian ini menekankan pentingnya pelayanan holistik dan merekomendasikan replikasi program dengan adaptasi kontekstual.